The Influence of Influencer Marketing, Customer Reviews, and Customer Ratings on Buying Interest in the Perspective of Human Resources (Study on Garnier Skincare Consumers in Dau District, Malang Regency) - Eko Agus Alfianto (CV. Satria Jaya, 2025)
This study aims to examine the influence of beauty influencers, customer reviews, and customer ratings on purchase intention toward Garnier skincare products. The research employs a quantitative approach using a survey method. Data were collected from 100 consumers of Garnier skincare products in Dau District, Malang Regency, selected through purposive sampling. The instrument used was a structured questionnaire measured with a five-point Likert scale. Data analysis was conducted using multiple linear regression supported by classical assumption tests. The results indicate that beauty influencers, customer reviews, and customer ratings simultaneously have a positive and significant effect on purchase intention. Partially, customer reviews and customer ratings have a positive and significant influence on purchase intention, while beauty influencers do not show a significant effect. Among the independent variables, customer ratings exhibit the strongest influence on purchase intention. These findings suggest that consumer-generated information plays a more crucial role than influencer endorsement in shaping purchase intention for skincare products